Effect of a fuselage boundary layer ingesting propulsor on airframe forces and moments - Fernández, Antonio Martínez; Smith, Howard (Elsevier, 2020)
The aim of this research project was to investigate the benefits of hybrid-distributed propulsion and boundary layer ingestion applied to an airliner similar in size, range and cruise velocity to an Airbus A320 or a Boeing 737-800. The power system selected consisted of two under-wing mounted conventional turbofans and an electrically driven boundary layer ingesting fan, located at the rear fuselage. The power required for the fan is extracted from both turbofans. The worked carried out and presented in this paper offers a new approach to modelling boundary layer ingestion configurations, consisting of using the sliding mesh method to simulate the rotation of the blades within the airflow. The simulations indicate that ingesting the boundary layer results in remarkable improvements reducing drag and increasing propulsive force, reaffirming the potential of this technology to reduce fuel consumption. However, the results also registered large changes in the pressure distribution, and hence in the pitching, rolling and yawing moment that need to be accounted for in the design phase.
Keywords: Aircraft Design; Boundary Layer Ingestion; Computational Fluid Dynamics